Factors Affecting Profitability in Telecommunication Sector Companies Listed on the Indonesia Stock Exchange for the Period 2016-2023 - Rizka, Auliah; Aryaningsih, Nabilah Risna; Budianto, Erwin (PT FORMOSA CENDEKIA GLOBAL, 2025)
The sustainability and growth of a company are strongly determined by its ability to generate profits. One key metric used to evaluate profitability is Return on Assets (ROA). To remain competitive and resilient, companies must regularly monitor and analyze their financial performance, including identifying the factors that influence ROA. This study examines the relationship between ROA and several financial indicators, namely the current ratio (CR), debt-to-asset ratio (DAR), total asset turnover (TATO), and sales growth (SG). The research utilized regression analysis on a sample of five companies within the Indonesian telecommunications subsector that met specific criteria during the 2016–2023 period. The findings reveal that sales growth does not significantly impact ROA, whereas current ratio, debt-to-asset ratio, and total asset turnover have a significant effect. The model explains 75% of the variance in ROA, with the remaining 25% attributed to other unexamined variables. These results suggest that asset efficiency, liquidity, and solvency are critical factors influencing the profitability of telecommunications companies, while sales growth alone does not directly enhance the ability to generate net profit from assets.